2015
DOI: 10.1097/mib.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of an Oral Inhibitor of the Purinergic Receptor P2X7 in Adult Patients with Moderately to Severely Active Crohnʼs Disease

Abstract: Our data suggest that the purinergic receptor P2X7 antagonist AZD9056 has the potential to improve symptoms in patients with moderate-to-severe CD combined with a beneficial risk profile. Although the lack in change of inflammatory biomarkers questions its anti-inflammatory potential, the results obtained in this study rather suggest P2X7 antagonism for the treatment of chronic abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 18 publications
0
107
0
2
Order By: Relevance
“…P2X7R activates the NLRP3 inflammasome in T cells, macrophages, dendritic cells, and neutrophils (Gombault et al, 2012). However, no studies have assessed the utility of P2X7R antagonists in humans with IBD except for one study in Crohn’s Disease (CD) patients (Eser et al, 2015). …”
Section: P2x7r In Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
See 2 more Smart Citations
“…P2X7R activates the NLRP3 inflammasome in T cells, macrophages, dendritic cells, and neutrophils (Gombault et al, 2012). However, no studies have assessed the utility of P2X7R antagonists in humans with IBD except for one study in Crohn’s Disease (CD) patients (Eser et al, 2015). …”
Section: P2x7r In Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…A randomized placebo-controlled, double blind, Phase IIa Study in 34 patients (24 AZD9056 and 10 placebo) was done to assess the safety and efficacy of an oral P2X7R antagonist, AZD9056 32 in adult patients with moderately to severely active CD (Eser et al, 2015). This is the first study done to evaluate a purinergic drug in IBD.…”
Section: Crohn’s Disease (Cd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Huge drug discovery efforts over the past few years have led to the discovery of numerous P2X7R antagonists [17], [41], [27]. Whilst clinical trials of the first two P2X7R antagonists against rheumatoid arthritis showed disappointing outcomes [26], [39], a more recent clinical trial shows promise in the therapeutic use of a P2X7R antagonist (AZD9056) in the treatment of moderate-to-severe Crohn’s disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…Agents that have shown efficacy in other GI conditions [e.g. chronic constipation (elobixibat, or A3309 ), inflammatory bowel disease (AZD9056 [Eser et al 2015] and 5-aminosalicylic acid [Feagan and Macdonald, 2012;Ford et al 2011])] may also be beneficial for patients with IBS, but further research is needed.…”
Section: Additional Agents For Treatment Of Ibsmentioning
confidence: 99%